2013
DOI: 10.1097/jcp.0b013e3182970490
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Histamine 2 Receptor Antagonism in Treatment-Resistant Schizophrenia

Abstract: Histamine has important functions as regulator of several other key neurotransmitters. Patients with schizophrenia have lower histamine H1 receptor levels. Since a case report in 1990 of an effect of the H2 antagonist famotidine on negative symptoms in schizophrenia, some open-label trials have been performed, but no randomized controlled trial. Recently, it was shown that clozapine is a full inverse agonist at the H2 receptor. We performed a researcher-initiated, academically financed, double-blind, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Although one small open-label study (Whiteford et al, 1995) reported no significant effects, two larger studies (Rosse et al, 1990;Deutsch et al, 1993) reported significant therapeutic effects in a group of patients with schizophrenia. A recent randomized double-blind, placebo-controlled study with famotidine in treatment-resistant schizophrenia showed statistically significant improvement in the positive and negative syndrome scale (Meskanen et al, 2013). H 2 receptor agonism blocks accommodation of firing and causes long-term potentiation in hippocampus and cortex (Selbach et al, 1997;Haas and Panula, 2003), which may lead to cognitive enhancement and be worthy of further study.…”
Section: F Clinical Pharmacologymentioning
confidence: 99%
“…Although one small open-label study (Whiteford et al, 1995) reported no significant effects, two larger studies (Rosse et al, 1990;Deutsch et al, 1993) reported significant therapeutic effects in a group of patients with schizophrenia. A recent randomized double-blind, placebo-controlled study with famotidine in treatment-resistant schizophrenia showed statistically significant improvement in the positive and negative syndrome scale (Meskanen et al, 2013). H 2 receptor agonism blocks accommodation of firing and causes long-term potentiation in hippocampus and cortex (Selbach et al, 1997;Haas and Panula, 2003), which may lead to cognitive enhancement and be worthy of further study.…”
Section: F Clinical Pharmacologymentioning
confidence: 99%
“…It may be no coincidence that antipsychotic drugs such as clozapine and olanzapin act, in least in part, through histamine receptors [36]. Indeed, a new generation of non-dopaminergic drugs to treat both PD and SCZ bind to histamine H2 receptors[6,13]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, levels of the histamine metabolite tele-methylhistamine in the cerebrospinal fluid are 2.6-fold higher in SCZ patients than in healthy individuals, suggesting abnormally high histamine turnover [12]. Histamine H2 antagonist therapy has shown clinical benefits for patients with SCZ without significant adverse effects in a recent placebo-controlled randomized clinical trial[13]. The same type of therapy has proven effective at treating levodopa-induced dyskinesia in an animal model of PD and in patients with PD [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…3. Three RCTs on famotidine augmentation in refractory schizophrenia 2,13,15 reported benefits on different outcome measures and to different extents (10%-27% superiority over placebo). 4.…”
Section: Clinical Pointsmentioning
confidence: 99%
“…Of the remaining 3 RCTs, 2,13,15 all with results favoring famotidine augmentation in antipsychotic-refractory schizophrenia, 1 13 could not be evaluated because the full text was not in English. One found that famotidine outperformed placebo by a large margin (27%), 15 and 1 found that famotidine outperformed placebo by only a small margin (10%), 2 which falls well below the threshold of most definitions of treatment response even in refractory schizophrenia. Only 1 RCT 2 presented a sound statistical plan, and no RCT corrected for type I errors arising from multiple testing.…”
Section: Clinical Pointsmentioning
confidence: 99%